Experimental investigation and predictive modelling of CO2 laser processing of wood-plastic composites (WPCs) - Sharizal Ahmad Sobri; Teoh Ping Chow; Tan Koon Tatt; Mohd Hisham Nordin; Andi Hermawan; Mohd Natashah Norizan (Results in Engineering)
Wood-plastic composites (WPCs) offer sustainable alternatives to solid wood, yet their heterogeneous nature complicates precision laser cutting. This study evaluates the effects of feed rate and gas pressure during CO2 laser machining on cut depth, heat-affected zone (HAZ), cutting profile, and surface quality of 18 mm-thick WPC samples (60% wood, 40% recycled HDPE). Using a 1500 W CO₂ laser, experiments employed a full factorial design with feed rates of 1000, 2000, and 3000 mm/min, and gas pressures of 1, 2, and 3 bar. Multivariate analysis of variance (MANOVA) indicated significant impacts (p < 0.001) of both parameters, revealing feed rate as pivotal for penetration and gas pressure for improving cut quality. Slow feed (1000 mm/min) allowed full penetration but produced a wide HAZ (∼1.2 mm). High feed rate (3000 mm/min) reduced HAZ (∼0.5 mm) and improved surfaces but limited penetration (∼9 mm). Increasing gas pressure significantly narrowed HAZ and enhanced cut cleanliness by effectively cooling and expelling debris. Regression models demonstrated high predictive accuracy (R² ≥ 0.96), confirming strong linear relationships between parameters and outcomes. Optimal conditions were identified: maximum depth at slow feed and moderate gas pressure (1000 mm/min, ∼2 bar), minimal HAZ and best surface finish at high feed with high gas pressure (3000 mm/min, 3 bar), and balanced performance at intermediate settings (∼2000 mm/min, 2 bar). Energy-based analysis indicated that specific energy input governs cutting efficiency, and linear correlations were established between energy and key quality metrics. This study provides essential guidance for optimizing laser machining of WPCs, promoting precision, reduced thermal damage, and sustainable manufacturing practices.